Interactive Student Worksheet on Probability Using Problem-Based Learning to Support Computational Thinking - Gustina Indah Widya Sari; Budi Mulyono; Hapizah Hapizah (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Twenty-first-century education requires students to develop computational thinking as a higher-order thinking skill needed to solve various problems systematically. However, this ability still needs to be strengthened through technology-enhanced and student-centred learning innovations. This study aimed to develop an interactive electronic student worksheet on probability based on Problem-Based Learning (PBL) that is valid and practical, and to examine its potential effects on supporting students’ computational thinking skills. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research was conducted at SMK Bakti Ibu 3 Palembang, involving Grade 10 students as the research participants. Data were collected through walkthroughs or expert validation, observations, questionnaires, learning achievement tests, and interviews. The results showed that the interactive electronic student worksheet obtained an average validity score of 4.18, which was classified as good based on the content, construct, and language aspects. The practicality test results were categorised as very good, with an average score of 4.63 based on responses from students and teachers. In addition, the test results indicated that 84.31% of the students achieved the Learning Objective Achievement Criteria. The analysis of students’ problem-solving processes and interview data also showed that the use of the interactive electronic student worksheet facilitated the development of computational thinking indicators, including decomposition, pattern recognition, abstraction, and algorithmic thinking. Therefore, the interactive electronic student worksheet on probability based on Problem-Based Learning was considered valid, practical, and potentially effective in supporting students’ computational thinking skills.